2017
DOI: 10.1021/jacs.7b02179
|View full text |Cite
|
Sign up to set email alerts
|

Local Structures and Heterogeneity of Silica-Supported M(III) Sites Evidenced by EPR, IR, NMR, and Luminescence Spectroscopies

Abstract: Grafting molecular precursors on partially dehydroxylated silica followed by a thermal treatment yields silica-supported M(III) sites for a broad range of metals. They display unique properties such as high activity in olefin polymerization and alkane dehydrogenation (M = Cr) or efficient luminescence properties (M = Yb and Eu) essential for bioimaging. Here, we interrogate the local structure of the M(III) surface sites obtained from two molecular precursors, amides M(N(SiMe)) vs siloxides (M(OSi(OBu))·L with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 114 publications
8
81
1
Order By: Relevance
“…DNP has been applied to characterize the surface of nanoparticles used for catalysis [124,184,192,238,268], biomaterials [106,107], cements [269], polymer fillers [85,210] and optoelectronics devices [158,159]. The investigated nanoparticles included functionalized silica [193,227,238,270], alumina [80,124,184,196,225,231,[271][272][273], silica alumina [192,233,234,274], ceria [195,275], sulfated zirconia [276], calcium silicate hydrates [269], phosphates [106,107,210], partially oxidized Sn nanoparticles [151] and crystalline semiconductors, such as CdSe, CdS or InP, in the form of nanoparticles (also called quantum dots) [158,159]. DNP has also been applied to investigate calcium silicate hydrates [269] and crystalline semiconductors, such as CdSe and CdS, in the form of nanosheets (also called nanoplatelets) (see Figure 24) [159].…”
Section: Nanoparticles and Nanosheetsmentioning
confidence: 99%
“…DNP has been applied to characterize the surface of nanoparticles used for catalysis [124,184,192,238,268], biomaterials [106,107], cements [269], polymer fillers [85,210] and optoelectronics devices [158,159]. The investigated nanoparticles included functionalized silica [193,227,238,270], alumina [80,124,184,196,225,231,[271][272][273], silica alumina [192,233,234,274], ceria [195,275], sulfated zirconia [276], calcium silicate hydrates [269], phosphates [106,107,210], partially oxidized Sn nanoparticles [151] and crystalline semiconductors, such as CdSe, CdS or InP, in the form of nanoparticles (also called quantum dots) [158,159]. DNP has also been applied to investigate calcium silicate hydrates [269] and crystalline semiconductors, such as CdSe and CdS, in the form of nanosheets (also called nanoplatelets) (see Figure 24) [159].…”
Section: Nanoparticles and Nanosheetsmentioning
confidence: 99%
“…Elemental analysis reveals a loading of 1.8 % (0.33 mmol Mn per g). IR Spectroscopy shows the presence of remaining Me 3 SiO group (Figure S10), as previously observed when trimethylsilyl amide derivatives are used as precursor . Although EPR measurements of 2 show a fairly complex pattern (Figures S10 and S11), with an unusual g factor of 2.80 for 2 , that is likely due to spin‐orbit coupling and symmetry of molecule, a broad line at g =2.09 is observed for 2@SiO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…IR Spectroscopy shows the presence of remaining Me 3 SiOg roup ( Figure S10), as previously observed when trimethylsilyl amide derivatives are used as precursor. [23,24] Although EPR measurements of 2 show af airly complex pattern (Figures S10 and S11), with an unusual g factor of 2.80 for 2,t hat is likely due to spin-orbit coupling ands ymmetry of molecule, [25] ab road line at g = 2.09 is observed for 2@SiO 2 .T he EPR signal of the manganese site free of organic ligand 2@SiO (FigureS12) is similar to that of 1@SiO with as inglei sotropic resonance andi dentical g = 2.01 (Figure S13), indicating as imilar environment after thermalt reatment and suggesting that monomeric Mn II sites could be present in both materials. The XANES spectra of 2, 2@SiO 2 ,a nd 2@SiO 2-400 ,s hare almost identicale dge energies and pre-edge features indicating that similar oxidation states and geometries are retained throughout (Figure 1b).…”
mentioning
confidence: 99%
“…33 It has recently been suggested that butene formation results from ethylene oligomerization. 49,50 To shed more light on the structure of our model system, we carried out XPS measurements. The O 1s signal in the pristine lms on Ru(0001) contains a main signal at 531.6 eV, assigned to oxygen atoms in the various Si-O-Si bonds in the lm, and a shoulder at 529.4 eV, assigned to chemisorbed O atoms on Ru(0001) ( Fig.…”
Section: (A) Model For the Phillips Catalystmentioning
confidence: 99%